Breakthrough - Dawson, Roxann; Nieporte, Grant; Franklin, DeVon; Metz, Chrissy, 1980-; Grace, Topher, 1978-; Lucas, Josh; Ruiz, Marcel; Haysbert, Dennis; Staab, Rebecca; Trammell, Sam, 1971-; Colter, Mike, 1976-; Smith, Joyce (Author at FaithWords (Firm)).; et al. (Beverly Hills, Calfornia : Twentieth Century Fox Home Entertainment, 2019)
Based on the inspirational true story of one mother's unfaltering love in the face of impossible odds. When Joyce Smith's adopted son John falls through an icy Missouri lake, all hope seems lost. But as John lies lifeless, Joyce refuses to give up. Her steadfast belief inspires those around her to continue to pray for John's recovery, even in the face of every case history and scientific prediction. A reminder that faith and love can create a mountain of hope, and sometimes even a miracle.
Originally released as a motion picture in 2019.
Based upon the book The Impossible by Joyce Smith with Ginger Kolbaba.
Wide screen (2.39:1).
Special features: A tapestry of miracles: Making breakthrough; "Carry my soul" Phil Wickham deleted scene, with optional commentary by DeVon Franklin and Roxann Dawson; Trapped in icy waters; audio commentary by DeVon Franklin and Roxann Dawson; gallery.
Music, Marcelo Zarvos ; film editor, Maysie Hoy ; production designer, Gae Buckley ; director of photograhpy, Zoran Popovic.
Chrissy Metz, Topher Grace, Josh Lucas, Marcel Ruiz, Dennis Haysbert, Rebecca Staab, Sam Trammell, Mike Colter.
Keywords: Smith, Joyce -- (Author at FaithWords (Firm)) -- Drama; Faith -- Drama; Accidents -- Drama; Mothers and sons -- Drama; Near-death experiences -- Drama; Missouri -- Social life and customs -- 21st century -- Drama